2021
DOI: 10.3390/cancers13133231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Obstruction Pulmonary Disease on Survival in Patients with Advanced Stage Lung Squamous Cell Carcinoma Undergoing Concurrent Chemoradiotherapy

Abstract: Background: To date, no data are available regarding the effect of chronic obstruction pulmonary disease (COPD) and COPD with acute exacerbation (COPDAE) on survival in patients with lung squamous cell carcinoma (SCC) receiving definitive concurrent chemoradiotherapy (CCRT). Patients and methods: We enrolled 3986 patients with clinical stage IIIA–IIIB, unresectable lung SCC, who had received standard definitive CCRT, and categorized them into two groups based on their COPD status to compare overall survival ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The potential mechanism of smoking-induced resistance to cisplatin is changes in the expression of drug influx and efflux transporters, decreased uptake, inactivation by nucleophilic compounds, or accelerated DNA repair in smoking-exposed urothelial cells [37,41,42]. Moreover, COPD has been associated with poor survival in lung and extrapulmonary cancer treatments [43][44][45][46]. Patients with cancer having COPD have worse survival than those without COPD [43][44][45][46][47] because COPD increases C-reactive protein levels, a biomarker of systemic inflammation, which is associated with an increased risk of cancer mortality, including for extrapulmonary cancers [47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential mechanism of smoking-induced resistance to cisplatin is changes in the expression of drug influx and efflux transporters, decreased uptake, inactivation by nucleophilic compounds, or accelerated DNA repair in smoking-exposed urothelial cells [37,41,42]. Moreover, COPD has been associated with poor survival in lung and extrapulmonary cancer treatments [43][44][45][46]. Patients with cancer having COPD have worse survival than those without COPD [43][44][45][46][47] because COPD increases C-reactive protein levels, a biomarker of systemic inflammation, which is associated with an increased risk of cancer mortality, including for extrapulmonary cancers [47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, COPD has been associated with poor survival in lung and extrapulmonary cancer treatments [43][44][45][46]. Patients with cancer having COPD have worse survival than those without COPD [43][44][45][46][47] because COPD increases C-reactive protein levels, a biomarker of systemic inflammation, which is associated with an increased risk of cancer mortality, including for extrapulmonary cancers [47]. Similarly, in the largest meta-analysis of its kind, Danesh and colleagues indicated that plasma fibrinogen, another nonspecific marker of systemic inflammation, is associated with both pulmonary and extrapulmonary cancers in smokers and never smokers [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 Thus, pre-existing COPD and current smoking status are highly prevalent in patients with OCSCC. 25,31 Smoking [32][33][34][35][36][37][38][39] and overwhelming comorbidity such as COPD [20][21][22][23][24] are independently associated with poorer survival in patients with cancer as well as greater resistance to cancer treatments such as radiotherapy or CCRT. Surgical complications or perioperative risk of morbidity and mortality also increase in patients with cancer because of current smoking status or COPD.…”
Section: Introductionmentioning
confidence: 99%